The fitness of the Brazilian damsel Stegastes fuscus is increased by sharing the territory with the dusky grouper Epinephelus marginatus - Bessa, Eduardo [UNESP] (Springer Heidelberg, 2011)
Stegastes fuscus and Epinephelus marginatus are known for co-habiting shelters. The damselfish S. fuscus uses the territory for nesting and must protect its eggs from grazers; the grouper E. marginatus is an omnivorous sit-and-wait predator. This study aims to evaluate the effect of juvenile groupers on the reproductive success of the Brazilian damsel. Twenty-five hours of underwater observations were done in So Sebastio and Ilhabela, Northern shore of So Paulo, Brazil. Fitness increase was measured by the egg-clutch area and number of contributing females in 130 nests shared by groupers and another 130 where damselfishes stood alone. An egg predator crab was placed into the damselfish territory, and behavioural responses during 2 min were recorded for nests with or without E. marginatus, 80 replicates each. Nests shared by the dusky groupers had more eggs and received eggs from more females too. While fathers who were alone in the territory had to deal with the egg predator crab, in shared nests, the grouper would take care of the intruder, sometimes feeding on it. Therefore, the Brazilian damsel may benefit from the presence of the dusky grouper by increasing the fitness and diminishing the costs of parental care.
Keywords: Reproductive behaviour; Rocky-shore fishes; Fish behaviour; Pomacentridae; Serranidae